O Parque Nacional do Araguaia: dilemas entre o desenvolvimento regional e a conservação da natureza (Revista de História Regional, 2020)
This article deals with the motivations and initiatives around the creation of the Araguaia National Park (PNA), with emphasis on the period between 1940 and 1960. For this purpose, several types of documentary sources, primary and secondary, were used: books, articles published in the media of the state of Goiás and the federal capital, official diaries of the state of Goiás and the National Congress, report from the Ministry of Agriculture and documents from the Fundação Brasil Central referring to Operation Bananal. The research led to the conclusion that there was a lot of ambiguity and diversity of motivations in the creation of the PNA, and that the way it started to be implemented disregarded the objectives of nature conservation. The prevailing view was contradictory to that defended by conservationists, who did not admit the human presence inside the park or the exploitation of its natural resources.Keywords: Araguaia National Park; conservation of nature; environmental history.